Torah revealed, Torah fulfilled: scriptural laws in formative Judaism and earliest Christianity - Neusner, Jacob (T & T Clark International, 2008)
Part I: Idolatry and paganism -- Scripture's account : idolatry and paganism / Baruch A. Levine -- Rabbinic reading : idolatry and paganism / Jacob Neusner -- Early Christian interpretation : the case of Justin Martyr / Bruce D. Chilton -- Part II: The Nazirite -- Scripture's account : the Nazirite / Baruch A. Levine -- Rabbinic reading : the Nazirite / Jacob Neusner -- The New Testament's interpretation : the Nazirite vow and the brother of Jesus / Bruce D. Chilton -- Part III: The sabbath -- Scripture's account : the Sabbath / Baruch A. Levine -- Rabbinic reading : the Sabbath / Jacob Neusner -- Early Christian interpretation : Sunday in the New Testament / Bruce D. Chilton -- Part IV: Dietary purity -- Scripture's account : dietary purity / Baruch A. Levine -- Rabbinic reading : clean and unclean foods / Jacob Neusner -- The New Testament's interpretation : Eucharist as holy food, mimesis of sacrifice / Bruce D. Chilton -- Part V: Sexual purity -- Scripture's account : sexual purity / Baruch A. Levine -- Rabbinic reading : sexual purity / Jacob Neusner -- Christian interpretation : sexuality and family / Bruce D. Chilton -- Part VI: Lex talionis -- Scripture's account : Lex talionis / Baruch A. Levine -- An eye for an eye : Lex talionis in Talmudic law / Baruch A. Levine -- The New Testament's interpretation : Jesus' Lex talionis / Bruce D. Chilton